AN ANALYSIS THE PRACTICE OF INDEPENDENT LEARNING CURRICULA AT SMK AL-KHOZINI - Istikomah, Lailatul; Budik Kusworo (Jurnal Tinta, 2023)
Independent Learning is a transformation of the education system to accommodate changes and progress of the nation that can adapt to the changing times. By restoring the essence of true education, namely education to humanize human beings or liberating education. Therefore, the freedom to innovate, learn independently, and create is carried out by the education sector, teachers, and students. The researcher focus how P5 applied at SMK AL-Khozini. The research approach used by researchers is descriptive qualitative. Data collection techniques are carried out by carrying out observations, interviews, quistionnaires and documentation. Then the researcher find the result of research which is: (1) Application of Independent Learning at SMK Al-Khozini, (2) Application the Projek Penguatan Profil Pelajar Pancasila (P5) at SMK Al-Khozini, (3) The Applied P5 Indicator, (4) Constraints on Implementing P5 and, (5) The Effect of Independent Learning Curricula (P5) for Student. The obstacle faced is school facilities. P5 is very important because it is like the spirit of Independent Curricula.